The Middle Byzantine Kanon-Notation of Manuscript H: A Paleographic Study with a Transcription of the Melodies of 13 Kanons and a Triodion - Biezen, Jan van (Bilthoven Creyghton, 1968)
Proefschrift ter verkrijging van de graad van doctor in de letteren aan de rijksuniversiteit te Utrecht.
Keywords: Middle Ages (500-1400); Plainchant; Manuscript; Paleography; Musical analysis; Canon